Offspring polymorphism and bet hedging: a large‐scale, phylogenetic analysis. (13th May 2020) - Scholl, Joshua P.; Calle, Leonardo; Miller, Nick; Venable, D. Lawrence
Abstract: Offspring polymorphism is a reproductive strategy where individual organisms simultaneously produce offspring that differ in morphology and ecology. It occurs across the Tree of Life but is particularly common among plants, where it is termed seed (diaspore) heteromorphism. The prevalence of this strategy in unpredictably varying environments has resulted in the assumption that it serves as a bet‐hedging mechanism. We found 101 examples of this strategy in southwestern North America. We provide phylogenetically informed evidence for the hypothesis that the occurrence of seed heteromorphism increases with increasing environmental variability, though this pattern was only significant for aridity, one of our two rainfall variability metrics. We provide a strong test of bet hedging for a large, taxonomically diverse set of seed heteromorphic species, lending support to the hypothesis that bet hedging is an important mechanistic driver for the evolution of seed heteromorphism. Abstract : We compile a large, taxonomically diverse (51 genera, 9 families) data set of southwestern North American seed heteromorphic species and infraspecific taxa (101). Using this dataset and modern phylogenetic comparative methods we find statistical support for the long‐standing hypothesis that seed heteromorphism functions as a bet‐hedging mechanism with respect to environmental unpredictability.